Behavior of Electrogalvanized Steel Pre-Treated with Cr(III)-Based Baths and Exposed to 0.5 M Na2SO4 Solution - Tomachuk, C. R. (2012)
As Cr (VI) compounds used to formulate conversion layers provide enhanced anticorrosive protection to zinc coatings, but they are produced using hazardous chemicals, the development of “green” technologies is a paramount purpose. Consequently, the corrosion behavior of zinc coatings subjected to a Cr3+ based passivating treatment, with and without sealing, was studied through EIS measurements in 0.5 M Na2SO4 solution. The analyses of the experimental data allowed inferring that the Cr3+-based conversion treatment with an adequate sealer provides good corrosion resistance and, coupled to an adequate painting system, could be a suitable alternative to traditional chromate coatings.